Rectangular Microstrip Patch Antenna at 2GHZ on Different Dielectric Constant for Pervasive Wireless Communication - Md. Maruf Ahamed; Kishore Bhowmik; Md. Shahidulla; Md. Shihabul Islam; Md. Abdur Rahman (Institute of Advanced Engineering and Science, 2012)
In this Paper presents the result for different dielectric constant values and the result is performed by thickness of 2.88mm and resonance frequency of 2GHz where 2.32 (Duroid) are gives the best result. In the recent years the development in communication systems requires the development of low cost, minimal weight, low profile antennas that are capable of maintaining high performance over a wide spectrum of frequencies. This technological trend has focused much effort into the design of a Microstrip patch antenna. The proposed antenna design on different dielectric constant and analyzed result of all dielectric constant between 1 to 10, when the proposed antenna designs on Duroid substrate with dielectric constant 2.32. At 2GHz the verify and tested result on MATLAB are Radiation Efficiency=91.99%, Directivity=5.4dBi, Directive gain=4.98dBi and Half Power Beam Width-H plane=99.6123 degrees.DOI:http://dx.doi.org/10.11591/ijece.v2i3.341